Antibiotic Sensitivity Against Klebsiella spp. in the Post Debridement Culture an Open Fracture in Emergency Department of dr. Soebandi Hospital Jember - Agustina, Dini; Cahyaningrum, Endiningtyas; Komariah, Cicih; Semita, I Nyoman; Putra, Yudha Ananta Khaerul (Indonesian Journal of Tropical and Infectious Disease, 2022)
Surgical site infection (SSI) in open fracture is often caused by bacterial contamination in the management of open fracture. Because of that, one of the most important thing in handling open fracture is debridement. Prophylactic antibiotics given are Cephalosporin and Aminoglycosides. Post-debridement culture is important in predicting the incidence of infection. One of the bacteria that is often found in post-debridement culture is Klebsiella spp. which can produce ESBL to fight β-lactam class of antibiotics. The purpose of this study was to determine antibiotic sensitivity against Klebsiella spp. in the post-debridement culture of cases of open fractures in the emergency department of dr. Soebandi hospital Jember. This study uses a laboratory exploratory research design. The sample of this study was the isolate of Klebsiella spp. which amounts to 5 from post debridement culture of open fracture patients in the emergency department of dr. Soebandi hospital Jember from March to May 2019.The method used is diffusion (Kirby Baurer) by matching using the CLSI standard table to determine sensitive, intermediate, or resistant. The results of this study showed that most antibiotics had resistance to Klebsiella spp., including β-lactam antibiotics, such as Amoxicillin, Ceftriaxone, Cefixime, Penicilin, Meropenem, and Cefadroxil. Vancomycin antibiotics are still sensitive to Klebsiella spp. in all patients. Gentamicin, Ciprofloxacin, Tetracycline, and Chloramphenicol antibiotics were sensitive in 1 patient. Erythromycin intermediates antibiotics against Klebsiella spp.. The conclusion of this study is that all β-lactam group antibiotics are resistant to Klebsiella spp while the most sensitive antibiotic is Vancomycin.